Are clinical measures of cervical flexor endurance, divided attention and dynamic visual acuity different in elite youth ice hockey players who report a previous history of concussion compared to those who do not?. Issue 5 (11th March 2013) - Schneider, Kathryn J; Emery, Carolyn A; Kang, Jian; Meeuwisse, Willem
Abstract : Objective: To evaluate differences in baseline measures of cervical flexor endurance (CFE), walking while talking (WWTT) and computerised dynamic visual acuity (cDVA) in elite youth ice hockey players who do and do not report a previous history of concussion. Design: Cross-sectional. Setting: Community ice rinks and sport medicine clinic in Calgary, Alberta, Canada. Participants: 532 Bantam (12–14 years) and Midget (15–17 years) ice hockey players. Assessment of Risk Factors: Previous history of concussion was reported on a preseason demographic questionnaire. Main Outcome Measurements: 458 players completed preseason tests of CFE, WWTT and cDVA (2011/12 hockey season). Results: Multivariate linear regression, adjusted for cluster, age group and sex was used to estimate mean differences in clinical measurement scores by concussion history (yes/no). There was no evidence of a difference in CFE score or cDVA scores at 85° per second. The mean time to complete WWTT complex compared to self-selected walking speed in midget females reporting a previous concussion was 3.10 s higher (95% CI 1.40 to 4.79) than in midget females not reporting a previous concussion. Players with previous concussion had significantly lower cDVA score at 120° per second than players without a previous concussion [cDVAleft =−0.033 logMAR (95% CI −0.064 to −0.0019); Bantam players cDVAright =−0.062 logMAR (95% CI −0.12 to −0.004). Conclusions: Tasks of divided attention decreased mean self-selected walking speed more in midget femaless with a previous history of concussion compared to those without. Computerised dynamic visual acuity at 120° per second was lower in players with a previous history of concussion. Acknowledgements: The University of Calgary Sport Injury Prevention Research Centre is one of the International Research Centres for Prevention of Injury and Protection of Athlete Health supported by the International Olympic Committee. We acknowledge the support of Alberta Innovates Health Solutions, the Alberta Children's Hospital Institute for Child and Maternal Health (Alberta Children's Hospital Foundation), and Talisman Energy.